The Relationship Between Pre-Service Teachers' Motivation to Teach and Curriculum Literacy - Aysel Ferah Özcan (Sakarya University, 2024)
This study aims to determine the relationships between teaching motivation and curriculum literacies. A total of 154 pre-service teachers studying in their final year at a state university participated in the study. Data were collected with the Motivation to Teach and Curriculum Literacies scales. This study was conducted in a relational survey model. Correlation and regression coefficients were calculated to analyze the study questions. Analyses were performed using SPSS 25.0. Findings revealed that there were moderate relationships between pre-service teachers' intrinsic motivation and assessment, subject matter knowledge, psychological foundation, and extrinsic motivation. It was determined that there was a high correlation between content knowledge and assessment basis. Extrinsic motivation was moderately related to psychological foundation and weakly related to other foundations of curriculum literacy. The relationship between the assessment and subject matter knowledge dimensions of curriculum literacy was found to be high. Motivation to teach explains curriculum literacy at a weak level. Intrinsic motivation was found to be one of the variables affecting subject matter knowledge and assessment literacy. Overall, the results suggest that the scope of curriculum literacy and other factors that may be associated with it need to be redefined.